A Study of the Effects of Active Smoking on Renal Function - Djabali Nacira; Berrezig Wiem; Ghai Djamila (Challenging Issues on Environment and Earth Science Vol. 3, 2021)
The aim of this study is to look into the effects of active smoking on kidney function. Toxic harmful effects of cigarettes come mainly from tobacco components; nicotine is against indications for kidney. The experiment was carried out at the hemodialysis service and the biochemistry laboratory. The service registry data has been used to determine the distribution of smokers and nonsmokers among dialysis patients. In the second part of the work, we studied the variations of the different parameters indicative of renal functioning (biochemical and haematological) between 22 smokers and 22 non- smokers who have no cardiovascular disease or diabetes. The findings indicate that smokers have a higher incidence of dialysis than nonsmokers. Smokers have higher levels of urea, creatinine, and uric acid, as well as lower blood albumin levels than nonsmokers. In smokers, there is a decrease in the amount of red blood cells and haemoglobin, as well as a rise in platelet count and erythrocyte sedimentation rate.